2018
DOI: 10.1016/j.lwt.2017.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid production and probiotic assessment of Lactobacillus plantarum isolated from Pico cheese

Abstract: Lactic acid bacteria isolated from a traditional Azorean cheese were screened for their ability to convert free linoleic acid to conjugated linoleic acid (CLA). Two strains of Lactobacillus plantarum were recognized as potential CLA producers. GC analysis identified cis-9, trans-11 C18:2 as the predominant isomer (10-14 µg/mL), followed by trans-9, trans-11 C18:2 (4-6 µg/mL). The CLA producing strains demonstrated strong biofilm capacity, high cell surface hydrophobicity and good auto-aggregation ability. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…According to Ribeiro et al (2018), CLA values can be related to factors such as temperature, fermentation time, linoleic acid content (LA). Some authors have shown a positive correlation between CLA formation and the ability to tolerate free LA, suggesting that is a detoxification mechanism (Adamczak et al 2008, Wang et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ribeiro et al (2018), CLA values can be related to factors such as temperature, fermentation time, linoleic acid content (LA). Some authors have shown a positive correlation between CLA formation and the ability to tolerate free LA, suggesting that is a detoxification mechanism (Adamczak et al 2008, Wang et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of L. rhamnosus PL60 to produce cis-9, tra-11 and tra-10, cis-12-CLA in humans was the first report indicating that probiotic bacteria produce CLA (172). Further studies showed that some Lactobacilli species isolated from GI tract of human and animals, including L. rhamnosus, L. acidophilus and L. plantarum, are CLA producers (173,174).…”
Section: Conjugated Linoleic Acid (Cla)mentioning
confidence: 99%
“…LAB isolated from traditional Azorean cheese were studied for their ability to convert free linoleic acid to CLA (Ribeiro, Stanton, Yang, Ross, & Silva, 2018). GC analysis identified cis ‐9, trans ‐11 C18:2 as the predominant CLA isomer in Azorean cheese produced using two potential CLA producing strains of Lb.…”
Section: Production Of Bioactive Compounds During Cheese Productionmentioning
confidence: 99%